Síntese do óxido de grafeno e incorporação do óxido de ferro visando suas aplicações em adsorção de corantes - Almeida, Anna Flávia de (2020)
Graphene oxide has physical, chemical and texture characteristics, which provide this material with an ability to adsorb impurities in the aqueous phase. In this way, this material was synthesized by the modified Hummers method and, through the co-precipitation method, the surface of the graphene oxide was modified with iron nanoparticles. Thus, iron oxide incorporated into graphene oxide was obtained. After these procedures, the materials were characterized with vibrational spectroscopy in the infrared region (FTIR), diffraction ray x (XRD), differential scanning calorimetry analysis (DSC), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), zero load point (pH PCZ) and nitrogen fission analysis (BET). The interpretations of these results propose that the iron oxide is incorporated externally to the surface of the graphene oxide, thus the material has become magnetic. In addition, the adsorption studies with the erythrosine dye were efficient. When analyzing the adsorption process for both adsorbents, he found that the best mathematical fit was Langmuir EXT. The graphene oxide incorporated into the iron oxide (OG. Fe3O4) showed a 20% reduction in the adsorvate absorption intensity and the graphene oxide (OG) indicated a decrease of 42.9%. Therefore, both the OG. Fe3O4 adsorbs the dye erythrosine, however, with a lower adsorption.